2016 10th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP) 2016
DOI: 10.1109/csndsp.2016.7574043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SSL security on bandwidth and delay in IEEE 802.11n WLAN using Windows 7

Abstract: Abstract-IPSec (IP Security) and SSL (Secure Socket Layer) are the main technologies for securing communications via the Internet. In this paper, we present new results on the performance of SSL using Windows 7 operating system under IEEE802.11n wireless network. Enabling IPSec security results on average approximately 50% less TCP throughout while enabling SSL security results on average approximately 96% less TCP throughput compared to open system. In IPSec, 3DES-SHA encrypted system outperformed AES128-SHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Impact of SSL security on network performance is evaluated in [8]. Results of these studies showed that IPSec and SSL lower bandwidth and increases RTT and CPU time.…”
Section: Related Workmentioning
confidence: 99%
“…Impact of SSL security on network performance is evaluated in [8]. Results of these studies showed that IPSec and SSL lower bandwidth and increases RTT and CPU time.…”
Section: Related Workmentioning
confidence: 99%